Meta-Analysis: Satu Dekade Penelitian Manajemen Laba di Indonesia - Nur Eny (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
This study aims to examine whether corporate characteristics and information asymmetry affects earnings management in Indonesia. This study use meta-analysis techniques approach with 35 samples from international and national accredited journals as well as Indonesian National Symposium of Accounting proceedings. Research results reinforce meta- analysis findings of previous studies where earnings management is done for different purposes. Management’s motivation to perform earnings management varies between opportunistic and efficient contract motives. Empirical evidence shows that corporate characteristics are predictors of earnings management. Cash flow from operations and information asymmetry significantly affect earnings management. This empirical evidence supports several previous meta-analysis in accounting field where moderator measurement variables has an effect on heterogeneity of research findings.